Analisis desain akustik ruang kelas Universitas Fajar Dalam meningkatkan kualitas belajar mengajar - Artayani, Meldawati; Nurdin Kasim, Noviar (Universitas Muslim Indonesia, 2017)
Noise is disturbing in teaching and learning, at a long intensity and a certain level can be harmful to health. The level of noise from an excessive location can have a kind of negative impact on people who often touch directly like hearing loss, comfort, lack of concentration and emotional disturbance. This study focuses on the study of acoustic material factors that affect noise in the classroom, while improving the quality of teaching and learning process is based on the comfort of the residents. The main objective of the study was to analyze the intensity of noise level within the classroom of the Dawn university classroom which was caused by the use of the room compiler material and compare the values ​​obtained with the standard noise level threshold based on KMLH Kep-48 / MENLH / 1996 November 25, 1996, and provide an alternative problem solving . This research is an experimental research using simple statistical analysis that is conducting direct observation in the field (Classroom C 205, C 208 and Classroom D207) and reporting carefully, thoroughly, systematically and accurately on the acoustic condition of the room. Data retrieval using sound level meter tool and the result is then calculated and evaluated.